2005
DOI: 10.1590/s0100-204x2005000900004
|View full text |Cite
|
Sign up to set email alerts
|

In vitro organogenesis in watermelon cotyledons

Abstract: -The objective of this work was to study the in vitro organogenesis of Citrullus lanatus, by the induction of adventitious buds in cotyledon segments cultured in medium supplemented with cytokinin. Explants were collected from one, three and five-day-old in vitro germinated seedlings, considering the distal and proximal cotyledon regions. The data obtained showed that in vitro organogenesis of watermelon occurred with higher efficiency, when cotyledon segments from the proximal region collected from three-day-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 18 publications
0
21
1
2
Order By: Relevance
“…Apparently, the effect of alternating darkness and light during seed germination on shoot regeneration from cotyledon varied in different species. Previous studies have shown that the frequency of shoot regeneration was influenced by the seedling age in cucurbits (Compton, 2000;Lee et al, 2003;Krug et al, 2005;Ntui et al, 2009). In the present study, the shoot regeneration frequency of cotyledons from 4-day-old seedlings was higher than those from 5 and 6-day-old seedlings.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Apparently, the effect of alternating darkness and light during seed germination on shoot regeneration from cotyledon varied in different species. Previous studies have shown that the frequency of shoot regeneration was influenced by the seedling age in cucurbits (Compton, 2000;Lee et al, 2003;Krug et al, 2005;Ntui et al, 2009). In the present study, the shoot regeneration frequency of cotyledons from 4-day-old seedlings was higher than those from 5 and 6-day-old seedlings.…”
Section: Discussioncontrasting
confidence: 44%
“…Many studies have demonstrated in vitro that low-salt, ½ and ¼ MS media promote shoot rooting in cucurbits (Lee et al, 2003;Han et al, 2004;Thomas and Sreejesh, 2004). Auxin is also widely used for root induction in cucurbits, including IAA (Han et al, 2004), NAA (Kathiravan et al, 2006;Kim et al, 2010) and IBA (Sarowar et al, 2003;Krug et al, 2005). All these observations revealed that the shoot rooting response may be affected by the growth medium composition.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the scare plant regeneration seems to be a consequence of infrequent differentiation of normal apical shoot meristems and not due to a defect in shoot development from available meristems as observed in earlier scanning electron microscopy studies on Capsicum (Wolf et al 2001). Interestingly, the development of adventitious 'blind leaves' has been reported in cotyledon explants of pepper (Wolf et al 2001) and in the members of Cucurbitaceae (Gaba et al 1999;Stipp et al 2001;Krug et al 2005).…”
Section: Discussionmentioning
confidence: 66%
“…Complementary anatomical analysis confirmed the atypical bud organization of the Brought to you by | MIT Libraries Authenticated Download Date | 5/11/18 5:35 PM majority of these structures as reported by Delis et al (2005). They may only be considered as leaf-like structures because their tissue is likely parenchymatous (Krug et al 2005). Few others are shoots or shoot-like structures because they have a classical meristem organization (Haensch 2004;Salaj et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The shoots and were more prone to rooting by increasing the subcultures. IBA is one of the most commonly used plant growth regulator for root induction in watermelon (Krug et al 2005) and other cucurbits, including summer squash (Pal et al 2007), ash gourd (Thomas and Sreejesh, 2004) and interspecific hybrid of Cucurbita (Sarowar et al 2003). In vitro-rooted plantlets were transferred to soil pot for acclimatization (Fig.…”
Section: Resultsmentioning
confidence: 99%